Balancing Discipline and Compassion: An Exploratory Study on Islamic Parenting Styles - Lubna Lutfia (Sekolah Tinggi Agama Islam Kuningan, 2025)
Parenting styles significantly influence child development, yet Muslim parents often struggle to balance Islamic disciplinary principles with compassionate child-rearing. This exploratory mixed-methods study examines how Islamic parenting styles integrate discipline and compassion, and their impact on child outcomes. Data was collected from 200 Muslim parents in Indonesia and Malaysia through surveys (adapted Parenting Styles and Dimensions Questionnaire) and in-depth interviews with 30 participants. Quantitative analysis revealed three dominant parenting styles: authoritative Islamic (62%), authoritarian (28%), and permissive (10%). The authoritative Islamic style showed the strongest positive correlations with children's emotional regulation (r = 0.53, p < 0.01), religiosity (M = 4.2/5), and parent-child communication (M = 4.5/5). Qualitative themes highlighted